Biogenesis of antibiotics-viewing its history and glimpses of the future - Spížek, J; Sigler, K; Řezanka, T; Demain, A (Folia microbiologica, 2016)
This review aims at comparing some historical data with the current situation in the study of biogenesis of natural compounds, antibiotics in the first place. Biogenesis of tetracyclines and cycloheximide and related compounds serves as example. Examples of molecular biological and bioinformatics methods used in the study of antibiotic biogenesis are described both in terms of its historical aspects and the current knowledge.
Keywords: metabolické sítě a dráhy; Metabolic Networks and Pathways; dějiny 20. století; Computational Biology; objevování léků; Drug Discovery; Anti-Bacterial Agents; History, 20th Century; dějiny 21. století; antibakteriální látky; History, 21st Century; výpočetní biologie